Efficiency and bureaucratisation of criminal justice: global trends - Johnston, Ed; Pivaty, Anna (Routledge contemporary issues in criminal justice and procedure, 2023)
"This book tackles the growing issues concerning the managerialism and bureacratisation of criminal justice systems across a number of jurisdictions. Here, managerialism means the move towards more standardised, bureaucratic and efficiency-driven systems, influenced by a desire to ensure predictability, control risks and, ultimately, economic savings via a more efficient process. The volume explores the phenomenon of managerialism in selected national criminal legal systems, covering all stages of criminal case processing from arrest to the imposition of sanction. The selected countries represent diverse socio-economic, political, cultural and legal traditions including common law, civil law, mixed common and civil law, and post-Soviet tradition. The book engages with a variety of relevant theoretical concepts, such as fairness, rationality, efficiency and legitimacy. The authors critically examine whether and to what extent the trend towards managerialism is indeed discernible, and what are its likely effects in the given national criminal legal systems. The book will be of interest to students, researchers and practitioners working in the areas of comparative criminal justice and procedure"--